PRINSIP FIRST TO FILE DALAM HUKUM HAK KEKAYAAN INTELEKTUAL DAN IMPLEMENTASI NYA DI INDONESIA - Mubarok, Rihan Fathurahman; Wahyudin, Rizky; Wiguna Mukti, Widiani Agustien; Suroya, Suci; Febrio , Reiky (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the first to file principle in Indonesia’s Intellectual Property system, focusing on its implementation in Law No. 13 of 2016 on Patents, Law No. 20 of 2016 on Trademarks and Geographical Indications, and Supreme Court Decision No. 161K/Pdt.Sus-HKI/2023. Employing a normative legal research design with statute, conceptual, comparative, and case approaches, the findings reveal that the first to file doctrine prioritizes formal filing order as the basis for exclusive rights, enhances legal certainty, and reduces inter-applicant disputes.